KAJIAN KEBIJAKAN PEMERINTAH KOTA SEMARANG DALAM PENGEMBANGAN EKONOMI KREATIF - Nana Kariada; Tri Martuti; Avi Budi Setiawan; Totok Sumaryanto F (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
The purpose of this research was to look at the development of the creative economy and to determine the priorities of the creative economy development strategy in the city of Semarang. This research uses descriptive analysis method. Data collection methods used are documentation and interviews. While the data analysis method used in this research is the analysis of overlay and analytic hierarchy process (AHP) to determine the policy strategy and development of the creative economy in the city of Semarang. The results of the research based on the overlay analysis show that the creative economy sector in the city of Semarang which is included in the leading sectors includes culinary, fashion and craft. Then for potential sectors are photography, videography, tv and radio, advertising, architects, music, applications, and games. From the results of interviews with creative industry players, it can be seen that the needs of creative economic actors in the city of Semarang include ease of business permits, moral support, especially embrace from the government, free space for work and expression and a marketing place for creative economic products. Based on AHP analysis, the results that the first priority aspect to be developed as an effort to progress in the creative economy in Semarang is an institutional aspect with a weight value of 70.9%. Then the second priority aspect is infrastructure with a weight value of 21.2%, and the last or third priority aspect is the policy aspect with a weighting value of 7.9%.